Prognostic indicators affecting functional outcome in Zone II flexor tendon repairs - Kannan, N.; Dhanaraju, S. (International Surgery Journal, 2018)
Background: Advances in surgical technique and rehabilitation have transformed zone II flexor tendon injuries from an inoperable no man's land to a standard surgical procedure. Despite these advances, many patients develop a substantial range of motion limiting adhesions after primary flexor tendon repair. To analyze the prognostic indicators, which influence the functional outcome in Zone II Flexor tendon injuries in fingers. Methods: 21 patients with 28 Zone II Flexor Tendon Injuries who presented to us within 24 hours since the injury and repaired primarily were studied. Postoperatively hand is immobilized in a dorsal POP splint for 3 weeks. Pulsed ultrasound therapy was started on day 7, and continued upto 8 weeks. Results: In the FFS Repaired group combined excellent and good results were obtained in 80% of patients. Zone II A good and excellent results were obtained in 81% of patients, whereas in II B in was 91%. In Zone II C60% of excellent and good results were obtained. Conclusions: High-frequency musculoskeletal ultrasound is a better investigation in the postoperative follow up to find out tendon adhesions and rupture and most importantly dynamic assessment.